Pengaruh Nilai Etika Kerja Islam, Motivasi, dan Lingkungan Kerja Terhadap Pendapatan Pegawai Bila Modiste - Rahmadita Marpaung, Mutiara; Wahyuni Lubis, Arnida; Samri Juliaty Nasution, Yenni (ILTIZAM Journal of Shariah Economics Research, 2023)
The purpose of this research was to find out how the influence of Islamic values of work ethics, work motivation, work environment on employee income in the Modiste, humans should also have technical skills and also demand knowledge that includes provisions and principles in Islam properly. also has moral character according to Islamic teachings on work motivation, work ethics, work environment, simultaneously and partially to the income of Bila Modiste employees. This research method is to use saturated sampling method which is a technique in determining the sample when all partisan populations are used as samples. There are two variables used in this study including the dependent variable namely work motivation, work ethics, work environment, then the independent variable is employee income . The result of the test applied is the simultaneous test showing that the dependent variable simultaneously influences the independent variable significantly. This is caused by the F count (20.713) > F table (4.76) and its significant value (0.001) < a (0.05), and it is concluded that work ethics variable X1 work motivation X2 work environment X3 can simultaneously affect employees.